AGREEMENT ON HUMAN RIGHTS IN CRIMINAL PROCEEDINGS - Alimkulov Y.; Nurmaganbet E.; Sabitova A.; Sanoj Razhan (Хабаршы. Заң сериясы, 2019)
In this article, the main forms of the criminal process are considered the concept of procedural agreement-one of the new institutions and modern ones. The effectiveness and economy of the criminal process of the modern humanitarian orientation and the objective of the procedural agreement that will promote the democratic development of our state is a great institution. In this article the authors of the global procedural agreement and domestic scientists believe, understandably, in comparison with the independent one is trying to open the exit. The Criminal Procedure Code, granted procedural agreement, as well as the types, forms, and features of their exploitation, the most, having examined the research work. In the Criminal Procedure Code, as provided in article 612 of the criminal cases committed in the framework of the investigation in cases where a minor, moderate or serious crime is a suspect, an ac-cused, caused at night, with the consent of the accused, in the form of a plea bargain; crimes committed by a criminal group, especially serious crimes committed by other persons, as well as extremist and ter-rorist crimes, the disclosure and investigation of crimes of all categories, is carried out in the form of an agreement on cooperation during the period of exposure. The purpose of the article – the theoretical and practical knowledge accumulated in this field, as well as in accordance with the norms of the Criminal Procedure Code, criminal procedural and criminal procedural legislation on cases, and the essence of the institution of appointment, is the disclosure of theoretical proposals to improve law enforcement practice in the agreement. The relevance of the topic Research in the course of a criminal process, a suspect, accused, defendant to defend the law, criminal procedure, increase efficiency, profitability, is determined by collateral. Based on the analysis of domestic and international experience, the authors attempted to analyze the institution of the procedural agreement during the analysis of the concept and form.